2020
DOI: 10.7759/cureus.8401
|View full text |Cite
|
Sign up to set email alerts
|

Stereotactic Radiosurgery and Stereotactic Radiotherapy for Malignant Skull Base Tumors

Abstract: The role of stereotactic radiosurgery/stereotactic radiotherapy (SRS/SRT) for malignant skull base tumors was summarized and discussed. The treatment of skull base tumors remains challenging. Their total resection is often difficult. SRS/SRT is one useful treatment option for residual or recurrent tumors after surgical resection in cases of primary skull base tumors. If skull base metastasis and skull base invasion are relatively localized, they can be candidates for SRS/SRT. Low rates of cervical lymph node i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 38 publications
0
5
0
Order By: Relevance
“…The median marginal doses of 12.7–20 Gy were used in these studies of GKS for chordoma from Table 3 . The clinical data from this table showed that the 5-year local control rate of chordoma after Gamma Knife treatment was 21.4%–76%, and the 5-year survival was 67-100 ( 1 , 7 , 11 20 ) ( Table 3 ). The tumor control rates from these clinical investigations varied widely, which demonstrated the radio-resistant characteristic of chordomas.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The median marginal doses of 12.7–20 Gy were used in these studies of GKS for chordoma from Table 3 . The clinical data from this table showed that the 5-year local control rate of chordoma after Gamma Knife treatment was 21.4%–76%, and the 5-year survival was 67-100 ( 1 , 7 , 11 20 ) ( Table 3 ). The tumor control rates from these clinical investigations varied widely, which demonstrated the radio-resistant characteristic of chordomas.…”
Section: Discussionmentioning
confidence: 99%
“…Although there is no doubt that neurosurgical therapy is the first line treatment option for the skull base chordoma, a total resection is often difficult to obtain, due to the invasion of the tumor into skull base and its location being adjacent to numerous important structures, along with a high tumor recurrence rate ( 7 ). The chemotherapy and traditional low-dose radiotherapy is not sensitive to this tumor ( 8 ).…”
Section: Introductionmentioning
confidence: 99%
“…Of various head and neck cancers, it is reported that the early-stage nasal and paranasal carcinomas [3][4][5] and early-stage external auditory canal carcinomas (EACCa) [1,2] rarely develop regional LN metastasis or cervical lymph node metastases [6]. Such patients might be good candidates for stereotactic radiosurgery (SRS)/SRT as an upfront therapy instead of surgical extirpation as the initial therapy [6].…”
Section: Discussionmentioning
confidence: 99%
“…Clump et al reported the efficacy of SRT, with the most common fractionated regimen being 24 Gy delivered in three fractions, which improved symptoms within one month [ 9 ]. Mori et al reported that if skull base metastasis and skull base invasion are relatively localized, they can be good candidates for SRT [ 10 ]. However, optimal treatment protocols or guidelines have not yet been established.…”
Section: Discussionmentioning
confidence: 99%